Specialization and Values as Inputs to Decision-Making Mining Managers - Drechsler, Herbert; Frost, Peter; Barnowe, J.; Chafetz, Israël (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1979)
This thrust of this paper is to explore the objectives which mining managers perceive as important for effective organizational functioning in terms of their values, of the sense they make of the world around them in two specific, fundamental areas, orientation toward people and toward things, and of the interaction between managerial values and this orientation.